Global random walk solvers for fully coupled flow and transport in saturated/unsaturated porous media. (June 2021) - Suciu, Nicolae; Illiano, Davide; Prechtel, Alexander; Radu, Florin A.
Highlights: Flow and transport equations for porous media are solved by new random walk schemes. Global random walk (GRW) algorithms are designed as L-schemes for Richards equation. The GRW L-schemes solve nonlinearities and model unsaturated/saturated transitions. The coupled flow-transport solvers are robust and second-order convergent in space. GRW schemes for both flow and transport are practically free of numerical diffusion. Abstract: In this article, we present new random walk methods to solve flow and transport problems in saturated/unsaturated porous media, including coupled flow and transport processes in soils, heterogeneous systems modeled through random hydraulic conductivity and recharge fields, processes at the field and regional scales. The numerical schemes are based on global random walk algorithms (GRW) which approximate the solution by moving large numbers of computational particles on regular lattices according to specific random walk rules. To cope with the nonlinearity and the degeneracy of the Richards equation and of the coupled system, we implemented the GRW algorithms by employing linearization techniques similar to the L -scheme developed in finite element/volume approaches. The resulting GRW L -schemes converge with the number of iterations and provide numerical solutions that are first-order accurate in time and second-order in space. A remarkable property of the flow and transport GRW solutions is that they are practically free of numerical diffusion. The GRW solvers are validated by comparisons with mixed finite element and finite volume solvers in one- and two-dimensional benchmark problems. They include Richards' equation fully coupled with the advection-diffusion-reaction equation and capture the transition from unsaturated to saturated flow regimes.